2020
DOI: 10.21608/ejchem.2020.47734.2975
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil Alleviates Rotenone-Induced Neurochemical changes and Striatal Neurodegeneration via Inhibiting Oxidative Stress and Neuroinflammation

Abstract: Objectives of study are around investigation the effect of the central nervous system stimulant modafinil on brain striatum neurodegeneration caused by subcutaneous (s.c.) rotenone administration in rats, further, the possible modulation by modafinil on L-dopa effect on oxidative stress, inflammation and nigrostriatal cell damage. Seven groups of Male albino mice received dimethyl sulfoxide s.c., rotenone (1.5 mg/kg, s.c., 3 times per week), rotenone/L-dopa (25 mg/kg, p.o., daily), rotenone/modafinil (0.1, 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…In this study, we found that rotenone increased nitric oxide levels and lipid peroxidation in the rat brain. Others have shown increased the level of nitric oxide in striatum and frontal cortex by rotenone [33,34]. We in addition, have demonstrated increased both iNOS and caspase-3 immunoreactivities in the striatum and SN, with loss of pigmented neurons, and markedly decreased tyrosine hydroxylase-immunoreactivity in rotenone-treated animas, which suggests a role for iNOS-derived NO in neuronal cell death caused by the toxicant [18,19].…”
Section: Discussionsupporting
confidence: 56%
“…In this study, we found that rotenone increased nitric oxide levels and lipid peroxidation in the rat brain. Others have shown increased the level of nitric oxide in striatum and frontal cortex by rotenone [33,34]. We in addition, have demonstrated increased both iNOS and caspase-3 immunoreactivities in the striatum and SN, with loss of pigmented neurons, and markedly decreased tyrosine hydroxylase-immunoreactivity in rotenone-treated animas, which suggests a role for iNOS-derived NO in neuronal cell death caused by the toxicant [18,19].…”
Section: Discussionsupporting
confidence: 56%